Femoral neck pseudoarthrosis in a polio patient treated with closed reduction and cell therapy. (April 2017) - Codesido, M.A.; Weil, Y.; Liebergall, M.; Mosheiff, R.; Khoury, A.
Abstract: Poliomyelitis disease affects the anterior horns cells of the spinal cord and certain motor nuclei of the brain stem. Paralysis type is flaccid and asymmetrical and result in muscular imbalance. Due to this, in case of having a hip muscles involvement, degenerative or posttraumatic, total hip arthroplasty is normally contraindicated because of the excessive risk of hip dislocation. In cases of subcapital femoral neck fractures the femoral head vascularization is a main concern, and in cases of neglected fracture with pseudoarthrosis the vascular status to the head must be investigated prior to further decisions. We report the case of a femoral neck fracture non-union after a missed femoral neck fracture in a polio affected leg treated with cannulated screws and percutaneous autologous injection of processed total nuclear cells (TNC) mixed with putty demineralized bone matrix.